Bart′s syndrome - Rajpal Aruna; Mishra R; Hajirnis K; Shah M; Nagpur N (Wolters Kluwer Medknow Publications, 2008)
A new-born girl presented with congenital absence of skin on the right leg and nail abnormalities. On second day of life, she developed multiple blistering skin lesions and died on seventeenth day of life. A positive family history of two other siblings, one male and one female who had blistering skin lesions and died within one and a half month of birth, was present. The diagnosis of Bart′s syndrome was made on clinical presentation, family history and skin biopsy.